Application of the Numbered Head Together Type Cooperative Learning Model to Improve Student Learning Outcomes in Mathematics Subjects - Dessi, Langga Cintia; Shah, Mansi (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to determine the increase in student learning outcomes in mathematics subjects, the subject of relationships between units, after implementing the Numbered Head Together (NHT) cooperative learning model for students. Methodology:This research uses Classroom Action Research. The research subjects in this study were third grade elementary school students. The research instruments are test questions, interview guide sheets, and observation guide sheets. Main Findings: The research results obtained in the first cycle were 8 students or 34.78% of students who completed their studies and 15 students or 65.21% who had not completed their studies with an average score of 49.13. In cycle II the number of students who completed increased to 16 students or 66.7% and those who had not completed decreased to 8 students or 33.3% with an average score of 62.5. In the implementation of cycle III, the number of students who completed it reached 22 students or 91.67% and only 2 students or 8.3% did not complete it with an average score of 85.20. Novelty/Originality of this study: The novelty of this research is the latest in this research is the selection of learning models, especially the Numbered Head Together (NHT) cooperative learning model. Through this NHT type cooperative learning model, students can freely express their opinions and learn to respect other people's opinions while still referring to the material and learning objectives so that they can improve student learning outcomes.